Regional Myo-inositol Concentration in Mild Cognitive Impairment Using 1H Magnetic Resonance Spectroscopic Imaging - Siger, Małgorzata (2009)
The goal was to assess regional patterns of metabolite abnormalities in mild cognitive impairment (MCI) and Alzheimer disease (AD) patients using proton magnetic resonance spectroscopy imaging at 1.5 Tesla. Fourteen MCI, 17 AD, and 16 healthy control (HC) subjects were studied. MCI was associated with higher myo-inositol (mIn) concentration in right parietal white matter compared with HC and lower mIn levels in frontal white matter compared with AD. AD was associated with higher mIn concentration in frontal and parietal white matter compared with HC. N-acetylaspartate (NAA) concentration of white matter was similar in all groups, whereas NAA concentration of gray matter showed a trend toward lower values in the right parietal lobe in AD compared with MCI and HC. A mIn increase in white matter in absence of significant NAA reduction suggests that mIn is a more robust and sensitive marker of white matter pathology in AD and MCI than NAA. Furthermore, the dissociation between mIn and NAA alterations in white matter could provide important information regarding the role of glial and neuronal damage in MCI and AD.